O velho-novo circo: um estudo de sobrevivência organizacional pela preservação de valores institucionais - Costa, Martha Maria Freitas da (1999)
The aim of this study was to identifie wich factors help to preserve the circus as an institution. Wich factors may have been important and responsible for its preservation and survival against ali adversities . The circus is an institution responsible over the years for entertainment and has its origins preindustrial era and has both family and coorporation caractheristics. The organization and practices of the circus today are considered of the next century. The results of this study showed that the circus preserve characteristics pre and pos industriais. The circus was able to preseve values and identity and also use ali the beneficies of the modern world. It will arrive to the century 21 as a strong and sui generis organization and very sucessfull. The tendency of ocupy the time with cultural activities place the circus as an excelent material of analysis.